Incidence and management of dystocia of dairy cows in Manoharganj upazila of Cumilla district, Bangladesh - Al Wasef; Md. Rashedul Islam (Universitas Airlangga, 2024)
Every year, thousands of cows and calves die during parturition for poor parturition managements, and insufficient veterinary services. A total of 83 cases of dystocia were the subject of a retrospective investigation between January 2021 and December 2023 to determine the incidence of dystocia in dairy cows in Manoharganj upazila of Cumilla district, Bangladesh. The study revealed that local breed cows had a higher prevalence of dystocia (53.01%) than cross-breed cows (46.99%). Also, younger cows had a higher incidence of dystocia (71.08%) than older cows. Primiparous heifers showed a higher incidence of dystocia (69.88%) than pluriparous cows (30.12%). In addition, compared with naturally inseminated cows (9.64%), artificially inseminated dairy cows had a higher dystocia rate (90.36%). The occurrence of dystocia was found to occur more frequently in fetal causes (65.06%) than in maternal causes (34.94%). Among maternal causes, incomplete cervix dilation was the most common (18.07%), while fetal head deviation was the most frequent fetal cause (27.71%). Fetal oversize, carpal flexion, shoulder flexion, fetal dropsy, twin calves, uterine torsion, and uterine inertia were other low-incidence causes of dystocia. The most common method of managing dystocia was manual correction (91.57%), followed by fetotomy (4.82%), and C-section (3.61%). After dystocia treatment, 96.25% of dams survived, and 3.75% of cases resulted in dam deaths; fetal death occurred in 32.5% of cases, while the fetal survival rate was 67.5%. Therefore, this study suggest that when using artificial insemination, it is best to consider the breed of the dam and sire.